Foreign Policy Behaviour of Small Power: A Study of Nepal - Baral, Bhim Nath (Journal of Political Science, 2022)
This article aims to analyze the foreign policy behaviour of Nepal, viewed from the lens of small power. The international system has remained under the dominance of greater powers despite numerous small powers. Most small powers have faced the problem of survival and it is their prime concern to protect sovereignty, territorial integrity and political independence. Several internal and external elements always threaten their interest. Nepal, a small South Asian country, is situated in a very sensitive region from a geostrategic point of view. It has its own determinants in its external behaviour. Nepal exhibited different behaviours in different modes of history by considering the matter of security and stability. However, history tells that a policy of independence, a policy of isolation, Indo-centric special relations, non-alignment, neutrality and balanced relation remained in practice in its foreign policy behaviour. The research is qualitative and data are collected from the secondary sources. It is prepared in descriptive and analytical design.